Recent Advances in Gout - Kurose, Rie (Rheumatology, 2020)
The purpose of this book is to provide an update on the epidemiology, pathophysiology, clinical symptoms, treatment, management, and ongoing research in gout. Accepted submissions are of high scientific value based on previous research and include novel and innovative research. This book is a valuable resource for physical clinicians who have the opportunity to treat gout. The scientific content of this book will be beneficial to patients, students, researchers, educators, and healthcare providers who are interested in the recent progress in gout research and therapy, not only physical clinicians.